Making an Arduino-Based Trash Disposal Game - Isidorus Ivan Kalya Wasistha; Ridwan Sanjaya; FX Hendra Prasetya (SISFORMA, 2024)
The problem that is going to be finished by the writer was the throwing trash activity where the writer will use Arduino as the tool for making ‘Throwing Trash Game” with purpose for making the throwing trash activity become more fun. On this essay, the writer will use waterfall method because the scope of this essay not really big and there is lot of testing that will happened during the making progress of the game. Overall, the writer wants to give some fun on throwing trash activity  using Arduino as the tool for making game and the writer hopes that the game the throwing trash activity become more fun.